Efektivitas Layanan Informasi dengan Format Klasikal Menggunakan Metode Small Group Discussion untuk Meningkatkan Self-Efficacy Akademik Siswa SMA Negeri 10 Padang - Wahid, Ahmad; Suhaili, Neviyarni (ARZUSIN, 2024)
Academic self-efficacy is one of the many factors that can affect student learning achievement. Someone who has good academic self-efficacy, will feel that he is always ready and alert in completing his academic tasks without any doubts about his condition. in completing their academic tasks without any doubts about their own condition. This study aims to see the effectiveness of the implementation of information services with a classical format using the small group discussion method to improve students' academic self-efficacy. This research uses a quantitative approach, with the type of research Quasi Experiment design The Non-Equivalent Control Group. The population in this study were Phase E students of SMA Negeri 10 Padang, sampling using purposive sampling method, then obtained samples of Phase E 4 and Phase E 9 classes. The technique used in data collection is by distributing questionnaires, then analyzed using the Wilcoxon Signed Ranks Test, and Mann-Whitney U 2 Independent Sample Test. The results of this study indicate that the implementation of information services with a classical format using the small group discussion method is effective in increasing students' academic self-efficacy. Specifically, the use of this method increases better academic self-efficacy.